Implementasi Aplikasi Perpustakaan Online Pada Sekolah Menengah Kejuruan Berbasis Model UML - Sari, Adika May; Yani, Desri (Forum Kerjasama Pendidikan Tinggi, 2020)
Implementation of a computerized book lending data collection system can run better and more efficiently than manual systems, and can minimize paper usage. Data collection systems such as borrowing and returning books are still done manually, namely by recording borrowing and returning transactions in the book. Manual recording method like this is considered less effective and efficient, because it can consume time and librarian personnel in terms of manual data collection. Therefore, with computers and the internet, by making an online library application it will be able to provide satisfying services for students and assist librarians in processing book data collection. Through a computerized data collection system such as building an online library application website, it can help librarians in the process of collecting data and making reports that are more effective and efficient, and can make it easier for students who want to find books and borrow books in the library more easily. So the implementation of the online library application website is a good solution to make it easier to solve this problem. In this study, a website was created to carry out borrowing transactions and book data collection in the library, then a search engine was created which made it easy for users to become books according to the title. This implementation uses the UML (unified Modeling Language) method, where the UML method will create class diagrams, use case diagrams, activity diagrams, to explain the behavior of the system to be used in library applications. whose function can produce a good website.